2018
DOI: 10.1007/s00894-018-3696-6
|View full text |Cite
|
Sign up to set email alerts
|

In silico identification of AChE and PARP-1 dual-targeted inhibitors of Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is a chronic neurodegenerative disease of the elderly that seriously affects the quality of life and the life expectancy of those affected. There is, as yet, no effective drug treatment of AD, although several acetylcholinesterase (AChE) inhibitors and a glutamate antagonist can provide relief from its symptoms. Recent studies have indicated that the overactivation of poly(ADP-ribose) polymerase-1 (PARP-1) may promote nerve cell death in the brains of AD patients, implying that PARP-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In the light of the multifactorially pathological mechanisms of AD, developing multitarget-directed ligands (MTDLs) may be a more promising approach for its treatment. Some researches and reviews of MTDLs for AD have already been reported 18 , 19 , but almost none of which is related to both PARP-1 and cholinesterase inhibitors 20 . In this regard, the PARP-1 and cholinesterase dual-targeted inhibitor of AD are worthy to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In the light of the multifactorially pathological mechanisms of AD, developing multitarget-directed ligands (MTDLs) may be a more promising approach for its treatment. Some researches and reviews of MTDLs for AD have already been reported 18 , 19 , but almost none of which is related to both PARP-1 and cholinesterase inhibitors 20 . In this regard, the PARP-1 and cholinesterase dual-targeted inhibitor of AD are worthy to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…When there is AD pathology present, activated PARP-1 encourages NF-kB to attach to DNA in microglia. Parallel to this, a number of studies have shown that inhibiting PARP-1 can halt the development of AD 91 92 93 94 . In mice lacking PARP-1, Aβ-induced microglial activation is reduced.…”
Section: Introductionmentioning
confidence: 92%
“…In the presence of AD pathology, activated PARP1 promotes the DNA binding of NF‐κB in microglia [63]. Similarly, a cluster of data has confirmed that PARP1 inhibition could delay the progression of AD [64,65]. Aβ‐induced microglial activation is mitigated in mice deficient for Parp1 [66].…”
Section: Parp1 and Alzheimer's Diseasementioning
confidence: 99%